Time-based expectations entail preparatory motor activity. (July 2017) - Volberg, Gregor; Thomaschke, Roland
Abstract: Human behavior is guided by expectations that facilitate perception of upcoming events or reaction to them. In natural settings expectations are often implicitly based on time, e.g., when making a phone call one would expect to hear either a person answering (earlier) or a voicemail greeting (later). We investigated how time-based expectations can improve performance in the absence of explicit prior information on the pending stimulus or the associated response. Visual stimuli were presented after a characteristic short or long foreperiod, and a forced-choice categorization using either the left or the right hand was required. The electroencephalogram (EEG) revealed a decrease in central 9–12 Hz power over the course of the trial. Moreover, lateralized pre-motor potentials were observed which changed polarity after the short foreperiod. At stimulus onset, amplitudes of pre-motor potentials co-varied with performance, so that higher (more negative) amplitudes were associated with slower responses to unexpected targets. Altogether, the results suggest that implicit time-based expectations entail effector-specific preparatory brain activity, which is inhibited until the expected onset time of the event. Thus, time-based expectations prepare for action.